REASONING FOR CREATING AN EDUCATIONAL TRAINING LABORATORY OF EDUCATION SPECIALISTS - Rostykus Надія; Boiko Галина (Journal of Information Technologies in Education (ITE), 2023)
The article elucidates the issue of creating the Educational Laboratory as a complex of educational institutions: a higher education institution – an institution of general secondary education; institution of higher education – institution of preschool education. On the basis of the analysis of domestic and foreign scientific works, it was found that the issue of the connection between theory and practice is considered in the aspect of organization and peculiarities of the students’ passage of various pedagogical practices. The reasons that affect the distance between theoretical training and practical training during internships by students of pedagogical specialties have been determined. The article describes the building of the Educational Laboratory, the key element of which is a glass wall with appropriate blackout, which allows students of higher education to observe the educational process in the classroom behind the glass wall, but the observing students cannot be seen or heard from the classroom. Laboratories that exist (scientific, creative, scientific and educational, laboratory of pedagogical skills, etc.) are presented in the articles as a union of the educational community for the organization of various types of scientific and methodical activities. The authors propose to create an educational laboratory for the training of specialists in the field of education, where student-teachers will have the opportunity to observe and to analyze the educational process (including after school hours) in preschool and general secondary education institutions under the guidance of scientific and pedagogical workers. At the same time, in the conditions of the Educational Laboratory, students of higher education will not affect the emotional and psychological state of students, since students will not be in the same classroom with students. According to the description, a drawing of the building of the Educational Laboratory is provided. The authors believe that the creation and functioning of the Educational Laboratory will contribute to ensuring the unity of theory and practice in the complex and integrated training of a high-quality and competitive specialist in the field of education.